Smart homes and health telematics : 12th International Conference, ICOST 2014, Denver, CO, USA, June 25-27, 2014, Revised papers /: 12th International Conference, ICOST 2014, Denver, CO, USA, June 25-27, 2014, Revised papers. (2015) - Unknown
No abstract available